2018
DOI: 10.3389/fpls.2018.00155
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of a Major QTL for Ceratocystis Wilt Disease in an F1 Population of Theobroma cacao

Abstract: Cacao is an important crop, its beans are key raw materials for the chocolate and cosmetic industries. Ceratocystis wilt of cacao (CWC) caused by Ceratocystis cacaofunesta is a lethal disease for the crop. Therefore, the selection of resistant cacao varieties is one of the viable ways to minimize losses in cacao production. In this paper, we described the identification of a major QTL associated with CWC in an F1 mapping population from a cross between a resistant, “TSH 1188,” and a susceptible genotype, “CCN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 58 publications
(70 reference statements)
0
7
0
Order By: Relevance
“…Introgression of QTLs into elite lines has been a successful strategy in annual crops with advanced breeding programs, like rice and maize 24 . Numerous QTLs have been published for cacao 20,2528 . But because of the long-generation times (2–4 years from seed to flowering), it could take decades to introgress a QTL into an elite cacao line, and remove the linkage drag from the QTL donor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Introgression of QTLs into elite lines has been a successful strategy in annual crops with advanced breeding programs, like rice and maize 24 . Numerous QTLs have been published for cacao 20,2528 . But because of the long-generation times (2–4 years from seed to flowering), it could take decades to introgress a QTL into an elite cacao line, and remove the linkage drag from the QTL donor.…”
Section: Discussionmentioning
confidence: 99%
“…Contigs representing the chloroplast and mitochondrial genomes were identified by comparing post-refinement contigs from the minimap assembly to the published cacao organelle genomes using nucmer 34 . The reads that mapped to these contigs were then reassembled with Circlator 25 . Coverages for each of these organelle genomes were much higher on average (~500× for mitochondrion and 1500× for chloroplast), which allowed for accurate correction with nanopolish 35 .…”
Section: Methodsmentioning
confidence: 99%
“…4-7). So far in the MP01 population, the maternal alleles have been reported as the ones more affecting the economically important traits, such as disease resistance 11,29 , and fat content and fatty acid composition 25 . Likewise, our study showed that the alleles from 'TSH 1188' are the ones controlling the QTL regions with a higher LOD scores, such as the one found on chromosome IV.…”
Section: Main Haplotypes Increasing Yield Components and Selection Ofmentioning
confidence: 99%
“…The female parent is related to Iquitos and Nanay genetic groups 13,24 , and the male parent has predominant ancestries from Iquitos, Criollo, and Amelonado 13,14,24 . Those parents contrast for many important traits, and the MP01 progenies segregate for disease resistance 11,29,51 , pod color 5 , fat content and fat composition 25 . The MP01 population also segregates for yield.…”
Section: Mp01 Segregating Mapping Populationmentioning
confidence: 99%
“…Theobroma cacao L. is one of the most important cash crops in many tropical regions of the world, with planted areas comprising ~8.2 million ha [ 1 ]. The nuts are used to make chocolate and cosmetics [ 2 ]. The cacao crop is the main source of income for millions of small farmers in many countries (e.g., Ivory Coast, Ghana, Ecuador and Brazil), who account for more than 80% of the global supply of cocoa [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%